2018
DOI: 10.4317/jced.54555
|View full text |Cite
|
Sign up to set email alerts
|

Association of liver enzyme levels and alveolar bone loss: A cross-sectional clinical study in Sado Island

Abstract: BackgroundThe interaction of periodontopathic bacteria with host immune system induces the production of inflammatory mediators which leads to alveolar bone loss (ABL), the essential feature of periodontitis. Concurrently, periodontal diseases cause the elevation of blood cytokine levels, the alteration of gut microbiota and the dissemination of enterobacteria to the liver. Owing to these mechanisms, periodontal disease might be a risk for liver dysfunction. Several epidemiological studies have reported associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Kuroki et al 41 recently studied the relationship between the levels of serum biomarkers (aspartate aminotransferase, alanine aminotransferase, and gamma‐glutamyl transpeptidase) and alveolar bone (assessed from panoramic radiographs) in 110 residents (mean age 73.3 years) on a Japanese island. Participants were divided into quartiles according to individual values of alveolar bone loss.…”
Section: Epidemiologic Relationship Between Periodontal Disease and Nonalcoholic Fatty Liver Disease In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuroki et al 41 recently studied the relationship between the levels of serum biomarkers (aspartate aminotransferase, alanine aminotransferase, and gamma‐glutamyl transpeptidase) and alveolar bone (assessed from panoramic radiographs) in 110 residents (mean age 73.3 years) on a Japanese island. Participants were divided into quartiles according to individual values of alveolar bone loss.…”
Section: Epidemiologic Relationship Between Periodontal Disease and Nonalcoholic Fatty Liver Disease In Humansmentioning
confidence: 99%
“… 21 , 22 , 23 Related to this, the concept of a gut‐liver axis and gut dysbiosis was further proposed as another potential route linking the oral cavity and the liver. 24 , 25 Since the late 2010s, systematic reviews and meta‐analyses 26 , 27 , 28 have continued to report on these associations based on growing evidence from epidemiologic studies 21 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 and on additional evaluation from in vivo research. 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 Moreover, as a next step, clinical studies with therapeutic intervention are expected to verify the effect of periodontal treatment on nonalcoholic fatty liver disease and nonalcoholic steatohepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study of Hispanics/Latinos reported no correlation between the prevalence of NAFLD and the clinical parameters of PD(16). Furthermore, a cross-sectional study of Japanese adults reported no correlation between PD and the biochemical parameters of NAFLD (35). Although there have been meta-analyses on the association between PD and NAFLD, they have contradictory ndings (15,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications on the association between liver enzymes and oral health are contradictory and are mainly focused on periodontitis. Some studies show no association between liver enzyme values and alveolar bone loss in patients without liver disease [31,32], while other studies show higher liver enzyme levels in patients with periodontitis [33,34]. Some studies hypothesize that periodontal disease might be a risk factor for the development of non-alcoholic steatohepatitis [35][36][37] and chronic liver disease [38].…”
Section: Discussionmentioning
confidence: 99%